Virtual and rapid manufacturing : advanced research in virtual and rapid prototyping - Proceedings of the International conference on advanced research in virtual and rapid prototyping (3rd., 24-29 September, 2009, Leiria, Portugal); Bartolo, Paulo Jorge (Lonfon, UK : Taylor & Francis, 2008)
22